3
$\begingroup$

Suppose $X_t$ is a jump-diffusion process with evolution given by $$X_t=X_0+\int_0^t a_s\,ds +\int_0^t b_s \, dWs + \sum_{i=1}^{N_t} \Delta X_i$$ where $a_t$ is the drift term

$b_t $ is volatility term

And $\Delta X_i$ corresponds to jump $i$ in the stock price. Then cont and tankov state that for a function $f(X_t,t)$ $$(1) \space\space\space df(X_t,t)=\frac{\partial f(X_t,t)}{\partial t}dt+a_t\frac{\partial f(X_t,t)}{\partial x} \, dt+\frac{b_t^2\sigma^2}{2} \frac{\partial f(X_t,t)}{\partial x^2} \, dt+\\ b_t\frac{\partial f(X_t,t)}{\partial x} \, dW_t+\left(f(X_{t-}+\Delta X_t)-f(X_{t-})\right).$$ Using this theorem for $f(\cdot)=\ln(\cdot)$ and $S_t$ described by the stochastic diff. eq. (below) $$\color{red} {\frac{dS_t}{S_t}=\mu dt +\sigma dW_t+dj}$$ we get $$(2) \space\space\space d\ln S_t =\frac{\partial \ln S_t}{\partial t}\,dt+\mu S_t \frac{\partial \ln S_t}{\partial S_t} \, dt+\sigma S_t\frac{\partial \ln S_t}{\partial S_t} \, dW_t+(\ln j_tS_t-\ln S_t) \\ \mu S_t\frac{1}{S_t} \, dt + \dfrac{\sigma^2S_t^2}{2} \left(\frac{1}{-S_t^2}\right) \, dt + \sigma S_t\frac{1}{S_t} \, dW_t + (\ln j_t+\ln S_t-\ln S_t)=\\ \left(\mu-\frac{1}{2}\right) \, dt+\sigma \,dW_t+\ln j_t$$ this is solved to give $$\ln S_t=\ln s_0 + \left(\mu-\dfrac{1}{2}\right)t+\sigma W_t + \sum_{i=1}^{N_t} \ln j_t$$ now my question is :how he apply ito differential to (1) by $f(x)=\ln x$ to obtain (2)...I am sorry to ask this question, but I can't use Ito formula to obtain (2).

I am thankful for your hint In advanced

$\endgroup$
5
$\begingroup$

The problem here is that you are using the Ito formula for Lévy processes – your process is not a Lévy process, but a semimartingale that is driven by a Lévy process (read the 8.3.4 – "Ito Formula for Seminartingales" in the Tankov book). For example, at a point $t$ where there is a jump $j_t$, your process doesn't satisfy $$ S_t = S_{t-} + j_t $$ but rather $$ S_t = j_tS_{t-} $$ More precisely, you process is a Dolean-Dades exponential of a Lévy process.

So you have to use Ito for semimartingales (proposition 8.19 in Tankov), i.e.

$$ \begin{align} f(t, X_t) - f(0, X_0) &= \int^t_0 \frac{\partial f}{\partial s}(s, X_s) ds + \int_0^t\frac{\partial f}{\partial x}(s, X_s) dX_s \\ &+ \frac{1}{2} \int^t_0 \frac{\partial^2 f}{\partial x^2}(s, X_s) d[X, X]_s^c \\ &+\sum_{s \leq t, \Delta X_s \neq 0} [f(s, X_s) - f(s, X_{s-}) - \Delta X_s\frac{\partial f}{\partial x}(s, X_s)] \end{align} $$ where $[X, X]_s^c$ is the quadratic variation of the continuous part of $X$.

This formula is less straight-forward to apply, because for example if you insert $S_t$ as $X_t$ and use $\log$ as $f$, then the second term on RHS is $$ \int_0^t\frac{\partial f}{\partial x}(s, S_s) dS_s = \int_0^t\frac{1}{S_t}S_t(\mu ds + \sigma dW_s + dj) = \mu t + \sigma W_t + \int^t_0dj $$ How do you interpret the last integral in this situation? It is actually an integral against the jump measure of $S_t$, $J_S(x, t)$. This is pure hand-waving, but for now I just argue that this is the sum of jumps up to time $t$: $$ \int^t_0dj = \int_0^t \int_\mathbb R xJ_S(ds, dx) = \sum_{s\leq t, \Delta S_s \neq 0} j_s $$ This part will cancel against the term $- \Delta X_s\frac{\partial f}{\partial x}(s, X_s)$ inside the sum in the Ito for semimartingales so that essentially, you will be left with the usual Ito for Lévy processes, except that the jump part will look like $$ f(X_t) - f(X_{t-}) $$ instead of $$f(X_{t-} + \Delta X_t) - f(X_{t-})$$ Thus, at a point where there is a jump, you get $$ f(S_t) - f(S_{t-}) = f(j_t S_{t-}) - f(S_{t-}) = \ln(j_t) + \ln(S_{t-}) - \ln(S_{t-}) $$


As for your solution attempt I'm not sure what you tried to do there – it seems you are trying to derive an Ito formula of your own. I suggest using the original formula with the said modification for the jumps.

Your process corresponds to $$ S_t = S_0 + \int^t_0 S_s \mu ds + \int^t_0 \sigma S_s dW_s + \sum S_s j_s $$ from which you can read off $a_t$, $b_t$, and then plug into the Ito formula. For example, $$ a_t \frac{\partial f(S_t, t)}{\partial x} dt = \mu S_t \frac{1}{S_t} dt = \mu dt $$

$\endgroup$
  • $\begingroup$ thanks a million $\endgroup$ – Khosrotash Jun 5 '17 at 0:24
  • 1
    $\begingroup$ @Khosrotash I removed that $[X, X]^c = t$. This was wrong, because I forgot you need the quadratic variation of a geometric BM, not regular BM. This doesn't affect the rest of the analysis though. $\endgroup$ – Slug Pue Jun 5 '17 at 6:14
  • $\begingroup$ I am wondering what it will happen if $J_t = 0$? If there is no jumps, the last term related to $\ln J_t$ should disappear. Is that because $S_{t}=S_{t-}(1+J_t)$ instead of $S_t = S_{t-}J_t$? $\endgroup$ – Shine Nov 30 '17 at 20:57
0
$\begingroup$

Is my work true ? $$f(x,t)=\ln x \to (It\hat{o} \space formula)\\ df=\frac{\partial f}{\partial t}dt+\frac{\partial f}{\partial x}dx+\frac12\frac{\partial^2 f}{\partial x^2}(dx)^2\\ df=0dt+\frac{1}{ x}dx+\frac12.\frac{-1}{ x^2}.(dx)^2$$ then put $dS_t=\mu S_tdt+\sigma S_tdW_t+S_tdj$ into $df$ $$d(\ln S_t)=0dt+\frac{1}{S_t}dS_t-\frac{1}{2S_t^2}(dS_t)^2=\\ 0dt+\frac{1}{S_t}\color{red} {(\mu S_tdt+\sigma S_tdW_t+S_tdj)}-\frac{1}{2S_t^2}(\color{red} {\mu S_tdt+\sigma S_tdW_t+S_tdj})^2=\\0dt+\mu S_t+\sigma W_t +dj-\frac{1}{2S_t^2}(\mu^2S_t^2dt^2+(\sigma S_tdW_t)^2+(S_tdj)^2+2\mu S_tdt\sigma S_tdW_t+2\sigma S_tdW_tS_tdj+2\mu S_tdtS_tdj)\\=$$ simplify ,and be ware of $$dt^2 \to 0 \\(dW_t)^2 \to dt\\dt.dW_t \to 0\\dW_t.dj \to 0 \\dj.dj\to 0 \\dj.dt \to 0 $$ $$\\0dt+\mu S_t+\sigma W_t +dj-\frac{1}{2S_t^2}(\sigma^2 S^2_tdt)$$ so $$dS_t=(\mu-\frac12 \sigma^2)dt+\sigma dW_t+dj$$ vs $$\left(\mu-\frac{1}{2}\right) \, dt+\sigma \,dW_t+\ln j_t$$ I don't now what happen for $dj \to d\ln j$ ? Hint at this point is needed !

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.